Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x.2013 - x = 2013 . 2011 + 2013
=> x(2013 - 1) = 2013.(2011 + 1)
=> x . 2012 = 2013. 2012
=> x = 2013 . 2012 : 2012
=> x = 2013
Bui Bao Ngoc oi! phan a,la (x+1)/10 hay x+(1/10)?
cac phan khac nua!
a) 75 : ( x - 18 ) = 52 = 25
=> x - 18 = 3
=> x = 21
b) 740 : ( x - 10 ) = 102 - 2 x 13
740 : ( x - 10 ) = 100 - 26 = 74
=> x - 10 = 10
=> x = 20
c) ( 2x - 5 )3 = 8 = 23
=> 2x - 5 = 2
=> 2x = 7
=> x= 7/2
d) ( 15 - 6x ) x 35 = 36
=> ( 15 - 6x ) = 36 : 35 = 3
=> 6x = 12
=> x = 2
Bài 1:
a: \(\Leftrightarrow3^x\cdot10=810\)
\(\Leftrightarrow3^x=81\)
hay x=4
c: \(\Leftrightarrow5^x\cdot5+5^x\cdot\dfrac{1}{25}=126\)
\(\Leftrightarrow5^x\cdot\dfrac{126}{25}=126\)
\(\Leftrightarrow5^x=25\)
hay x=2
Bài 2:
a: \(27^{11}=3^{33}\)
\(81^8=3^{32}\)
mà 33>32
nên \(27^{11}>81^8\)
c: \(625^5=\left(5^4\right)^5=5^{20}\)
\(125^7=\left(5^3\right)^7=5^{21}\)
mà 20<21
nên \(625^5< 125^7\)
x . 3 = 8
x = 8 : 3
x = \(\frac{8}{3}\)